The Practices of Human Genetics
XIV, 218 p.
Keywords: That concern about human genetics is at the top of many lists of issues requiring intense discussion from scientific, political, social, and ethical points of view is today no surprise. It was in the spirit of attempting to establish the basis for intelligent discussion of the issues involved that a group of us gathered at a meeting of the International Society for the History, Philosophy, and Social Studies of Biology in the Summer of 1995 at Brandeis University and began an exploration of these questions in earlier versions of the papers presented here. Our aim was to cross disciplines and jump national boundaries, to be catholic in the methods and approaches taken, and to bring before readers interested in the emerging issues of human genetics well-reasoned, informative, and provocative papers. The initial conference and elements of the editorial work which have followed were generously supported by the Stifterverband fUr die Deutsche Wissenschaft. We thank Professor Peter Weingart of Bielefeld University for his assistance in gaining this support. As Editors, we thank the anonymous readers who commented upon and critiqued many of the papers and in tum made each paper a more valuable contribution. We also thank the authors for their understanding and patience. Michael Fortnn Everett Mendelsohn Cambridge, MA September 1998 vii INTRODUCTION In 1986, the annual symposium at the venerable Cold Spring Harbor laboratories was devoted to the "Molecular Biology of Homo sapiens.